CHARACTERISTICS OF AMBULATORY BLOOD PRESSURE MONITORING IN PATIENTS WITH ACUTE HEART FAILURE - Thị Mai Hương, Nguyễn; Văn Bé Hai, Nguyễn; Thị Phương Dung, Nguyễn; Thanh Huân, Nguyễn (Journal of Health and Aging, 2025)
The use of ambulatory blood pressure monitoring (ABPM) has been established in the evaluation of the 24-hour blood pressure (BP) pattern. Most studies have examined the nighttime blood pressure fall (NBPF) pattern in patients with chronic heart failure (CHF). However, little clinical information is available to understand the pattern of NBPF in patients with acute heart failure (AHF). Objective: to investigate the pattern of ABPM in patients with AHF. We included 69 patients with HFrEF who were hospitalised for AHF at Department of Cardiology, Thong Nhat Hospital from March 2020 to December 2021. After haemodynamic stabilisation, we monitored the patients ambulatory BP. The patients mean age was 66.2±14.77 years, with 71.0% of men, and a mean heart failure duration of 2.8±1.9 years. Coronary artery disease was the most common cause of heart failure (79.7%), while dilated cardiomyopathy accounted for 20.3%. The comorbidities were: hypertension, dyslipidemia, diabetes, stroke, and atrial fibrillation; 97.1%, 91.7%, 31.9%, 10.1%, and 31.9%, respectively. The New York Heart Association functional classification was: II, III, and IV; 17.4%, 63.8%, and 18.8%, respectively. The therapeutic regimens were as follows: angiotensin receptor neprilysin inhibitor, angiotensin converting enzyme inhibitor/angiotensin receptor antagonist, beta-blockers, spironolactone, and digoxin; 20.3%, 69.6%, 68.1%, 85.5%, and 34.8%, respectively. Four patients (5.8%) had normal BP dipping pattern (NBPF ≥10%), 35 (50.7%) had a non-dipping pattern (0% ≤NBPF <10%), and 30 (43.5%) had a riser pattern (NBPF <0%). Our findings highlight the haemodynamic pattern of patients with AHF with most of them showing an NBPF below 10%.